Analysis and Modeling of Rat Gait Biomechanical Deficits in Response to Volumetric Muscle Loss Injury - Dienes, Jack A.; Hu, Xiao; Janson, Kevin D.; Slater, Conrad; Dooley, Emily A.; Christ, George J.; Russell, Shawn D. (Frontiers in Bioengineering and Biotechnology, 2019)
A substantial amount of research is underway to develop more effective approaches for the regeneration of functional muscle tissue as treatment for volumetric muscle loss (VML) injury, but few studies have evaluated the relationship between injury and the biomechanics required for normal function. To address this knowledge gap, the goal of this study was to develop a novel method to quantify the changes in gait for rats with tibialis anterior (TA) VML injuries that identifies biomechanical and kinematic changes in response to injury as well as during recovery. Control rats and rats with surgically-created VML injuries were affixed with motion capture markers on the bony landmarks of the back and hindlimb and were recorded walking on a treadmill both prior to and post-surgery. Data collected from the motion capture system was exported for post-hoc analysis in OpenSim and Matlab. In vivo force testing indicated that the VML injury resulted in a significant deficit in force generation ability. Analysis of joint kinematics showed significant differences at all three post-surgical timepoints and gait cycle phase shifting, indicating augmented gait biomechanics in response to VML injury. In conclusion, this method identifies and quantifies key differences in the gait biomechanics and joint kinematics of rats with VML injuries and allows for analysis of the response to injury and recovery. The comprehensive nature of this method opens the door for future studies into dynamics and musculoskeletal control of injured gait that can inform the development of regenerative technologies focused on the functional metrics that are most relevant to recovery from VML injury.